Reporting observational studies in veterinary research: turkish adaptation of the strobe-vet criterias - Tuba Balak; Feyza Günay; Özlem Kaymaz; Mustafa Bahadır Çevrimli; Doğukan Özen; Mustafa Agah Tekindal (Eurasian Journal of Veterinary Sciences)
Aim: This study, the Turkish version of the STROBE-VET was made to strengthen the reporting of observational studies in the veterinary field and making the usage of the STROBE-VET better understood by the researchers. Materials and Methods: STROBE-VET criteria have been translated into Turkish by 4 researchers (TB, FG, ES, MAT), each independent from the other. The translation was finalized with the collection of the group. Then, an expert translator was reversed and its compliance with the criteria was evaluated. Secondly, in order to assess the Turkish control list whether it is understood correctly by the researchers, 20 studies in the field of veterinary sciences have been evaluated by two veterinarians (DÖ and MBÇ). The correspondence between the responses of the researchers was examined using the percentage of compliance between researchers for each criterion. In addition, it was assessed using the Bland-Altman Method and the Intraclass Correlation Coefficient (ICC) using the total number of reported criteria. Results: According to results, criteria has a great variation in the frequency of reporting in the studies. ICC values ranged from 0.351 to 0.890. Conclusion: The Turkish version of STROBE-VET will be a guide for the referees and editors of journals as well as researchers studying in the field of veterinary science.